PENGARUH MODAL KERJA TERHADAP NET PROFIT MARGIN PADA PT. PARADISE JASMIN PALEMBANG - Kusminaini Armin; S Sahila (Fakultas Ekonomi Universitas Tridinanti Palembang, 2020)
This study aims to determine the effect of working capital on the net profit margin of PT. Paradise Jasmin. This research is a quantitative research. The population in this study is the overall financial statements of PT. Paradise Jasmin in the year (2013-2017), while the sample in this study was the balance sheet and income statement in the year (2013-2017). Data collection techniques are done by interview and observation techniques. The data analysis technique used is simple linear regression. The results of this study indicate that working capital has a positive and not significant effect on Net Profit Margin on PT.Paradise Jasmine.Keywords: Working Capital, Net Profit Margin